THE IMPORTANCE OF RISK FACTOR ASSESSMENT IN PREVENTING SEXUAL VIOLENCE AGAINST CHILDREN AND TEENAGERS - Lucca, Roger de [UNESP]; Castro Leao, Andreza Marques de [UNESP]; Silva, Renan Antonio da (Fundacao Univ Tocantins, 2022)
Sexual violence against children and adolescents is one of the forms of rights violation with the greatest impact on development, as it can cause severe damage of different orders, and is therefore considered by the World Health Organization (WHO) as a global public health problem. Thus, through this work, we seek to contribute in a relevant way to the achievement of preventive proposals, because, based on the application of specialized material for the assessment of possible risk factors for the incidence of sexual violence among children and adolescents, the implementation of a practice is facilitated. preventive professional This article was taken from the master's thesis that proposes to build an inventory of risks and protection for the incidence of juvenile sexual violence and aims to assess the positive contribution of the survey of risk factors for its occurrence, aiming to provide greater understanding and consistent elements for action.
Keywords: Children and Adolescent Sexual Violence; Sex Education; Personal Risks for Sexual Violence; Social Risks for Sexual Violence